2011
DOI: 10.1111/j.1553-2712.2011.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Coronary Artery Calcium Scoring Add to the Predictive Value of Coronary Computed Tomography Angiography for Adverse Cardiovascular Events in Low‐risk Chest Pain Patients?

Abstract: Objectives: Coronary angiography calcium score (CACS) is included for patients who receive coronary computed tomography angiography (CTA) as part of diagnostic testing for low-risk chest pain. Both tests add radiation exposure, and it is unclear whether the combination provides more information than either test alone. The objective was to asses if CACS = 0 determines freedom from coronary artery disease (CAD) and whether the addition of CACS to coronary CT angiography provides additional risk stratification in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…A total of 72 patients had a CACS of 0, among whom 14 (19%) had at least 1 stenosis ≥50%. Chang et al 92 found that 4 of 17 patients (24%) with a CACS of 0 still had CAD. Within the CON-FIRM registry (Coronary Computed Tomography Angiography Evaluation for Clinical Outcomes: An International Multicenter Registry), >5000 patients had a CACS of 0, yet 16% of these patients still had evidence of CAD on coronary CTA.…”
Section: Calcium Score Alonementioning
confidence: 99%
“…A total of 72 patients had a CACS of 0, among whom 14 (19%) had at least 1 stenosis ≥50%. Chang et al 92 found that 4 of 17 patients (24%) with a CACS of 0 still had CAD. Within the CON-FIRM registry (Coronary Computed Tomography Angiography Evaluation for Clinical Outcomes: An International Multicenter Registry), >5000 patients had a CACS of 0, yet 16% of these patients still had evidence of CAD on coronary CTA.…”
Section: Calcium Score Alonementioning
confidence: 99%
“…Of note, half of those with zero CACS and an adverse outcome had increased troponin measured by conventional assays (5,(8)(9)(10).…”
mentioning
confidence: 99%
“…Initially, 952 articles were identified for screening, 81 met criteria for full‐text review, and 33 articles were included in this meta‐analysis. Of the 33 studies, seven were randomized controlled trials, 30–36 17 were prospective cohort studies, 37–53 and the remaining nine were retrospective cohort studies 54–62 …”
Section: Resultsmentioning
confidence: 99%